An Efficient Multidocument Blind Signcryption Scheme for Smart Grid-Enabled Industrial Internet of Things. (21st February 2022) - Abdullah, Ako Muhammad; Ullah, Insaf; Khan, Muhammad Asghar; Alsharif, Mohammed H.; Mostafa, Samih M.; Wu, Jimmy Ming-Tai
Abstract : The smart grid-enabled industrial Internet of Things (SG-IIoT) is a hybrid data communication network connected with the power grid that collects and analyzes data from transmission lines, distribution substations, and consumers. In the IIoT setting, SG provides predictive information to its supplier and customers on how to effectively manage the power based on this aggregated data. To achieve this goal, every virtual or physical entity in the SG-IIoT must be linked and accessible over the Internet, which can be susceptible to numerous cyberattacks. In this paper, we propose a multidocument blind signcryption scheme to simultaneously resolve the security and efficiency issues. The proposed scheme performs the blind signature and encryption operation on multiple digital documents in one step because SG-IIoT outputs a large amount of data that needs to be blind signed and encrypted in a batch. The proposed scheme employs the concept of hyperelliptic curve cryptography (HECC), which is lightweight owing to the smaller key size. The comparative analysis in both security and efficiency with the relevant existing scheme authenticates the viability of the proposed scheme.